FAKTOR PENYEBAB KENAKALAN REMAJA DI DESA BUKIT MARATUR KECAMATAN SIANTAR MARTOBA KOTA PEMATANG SIANTAR - Rapika Susanti Marpaung; Sumardi Sumardi; Desti Irja (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the factors that cause juvenile delinquency in at bukit maratur village subdistrict siantar martoba city pematang siantar. This research type is descriptive with quantitative approach. The population in this study are adolescents who live in the village of at bukit maratur village subdistrict siantar martoba pematang siantar city, amounting to 45 people. The sampling technique was determined based on Isaac and Michael table with 5% error level, so the sample in this research is 40 people. The instrument used in this study is a questionnaire containing 43 statements about factors causing juvenile delinquency in the village of hill maratur siantar martoba subdistrict siantar siantar city, with indicators of factors from within self, family factors, environmental factors society, the factor of the school, consists of 7 sub indicators are divided into 14 dimensions. The result of data analysis shows that the factor of juvenile delinquency in at bukit maratur village subdistrict siantar martoba pematang siantar city, is observed from the factor in the self itself on the sub self control indicator is high with the percentage value of 72.99%. On the sub indicator of moderate / moderate sufficiency, the percentage of 54.00% and the sub-indicator of the lack of basic religious beliefs is high with the percentage of 66.99%. Viewed from family environmental factors on sub indicators less affection is high with percentage 69.16%. In sub indicators of family life is not harmonious also quite high with a percentage of 64.87%. Judging from environmental factor of society on sub environmental indicator is not conducive pertained to high with percentage value 67,62% while viewed from factor originating from school on sub indicator of teacher factor enough / moderate with percentage 55.49%. Based on the results of the research can be seen that the factors causing juvenile delinquency in the village of Bukit Maratur Siantar Martoba Subdistrict Pematang Siantar City is the most dominant factor derived from the environment community on sub environmental indicators that are not conducive to the dimensions of high crime.Keywords: Factors causing juvenile delinquency, siantar martoba